The effect of sports massage on state anxiety in elite soccer players - Taskin, Mine; Korkmaz, Erol; Budak, Maya; Sahin, Ibrahim Halil; Taskin, Halil (Frontiers in Psychology, 2025)
BackgroundA sports massage represents an intervention that is frequently used in sports for that purpose, to recover and prepare an athlete for the following match. Studies that link massage and psychological mechanisms are scarce. In the athletic and recreational sport population, most of the studies confirmed a positive correlation between a massage and the improvement of different psychological states. This study was conducted to evaluate the effectiveness of Sports Massage intervention on pre-match anxiety.MethodsA total of 26 elite soccer players participated in this study and were pretest and posttest by using the Quasi-Experimental study design, quantitatively. The instrument used in this study was State–Trait Anxiety Inventory (STAI). The state anxiety inventory was administered to the soccer players 30–45 min before the competition. There were two phases of instrument measurement in this study namely pre-massage (pretest) and post-massage (posttest).ResultsBinary logistic regression analysis was performed. There was a significant difference in the between pre massage anxiety and post massage anxiety (p < 0.05). Thus, the logistic regression model was effective in predicting the relationship between massage intervention and with reduction of anxiety. In a complementary logistic model, the odds of high anxiety were lower after massage (OR = 0.85; 95% CI) and ROC analysis yielded AUC = 0.76. Post-massage STAI-State scores were lower than pre-massage (mean ± SD: 28.35 ± 5.36 vs. 35.15 ± 7.70); we report the effect size (Cohen’s d value = 1.03) and 95% CI for interpretability.ConclusionThe study found that pre-match massage significantly affected the state anxiety of elite soccer players. Soccer players who had a massage showed 0.849 times smaller anxiety scores than did the players who had not. This finding suggests the efficacy of sports massage as an effective intervention to reduce pre-competition anxiety in elite soccer players.